Atomistic insights into the nucleation and growth of platinum on palladium nanocrystals - Wenpei Gao (Nature Portfolio, 2021)
Creating predictable, controllable nanoparticles relies on a mechanistic understanding of their synthesis. Here, through integrated in situ liquid microscopy and first-principles calculations, the authors elucidate the atomistic details involved in the formation of colloidal core-shell nanoparticles.